Revealing the Proteome of Motor Cortex Derived Extracellular Vesicles Isolated from Amyotrophic Lateral Sclerosis Human Postmortem Tissues - Natasha Vassileff; Laura J. Vella; Harinda Rajapaksha; Mitch Shambrook; Amirmohammad Nasiri Kenari; Catriona McLean; Andrew F. Hill; Lesley Cheng (Cells, 2020)
Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative disease characterized by the deposition of misfolded proteins in the motor cortex and motor neurons. Although a multitude of ALS-associated mutated proteins have been identified, several have been linked to small extracellular vesicles such as exosomes involved in cell−cell communication. This study aims to determine the proteome of extracellular vesicles isolated from the motor cortex of ALS subjects and to identify novel ALS-associated deregulated proteins. Motor cortex extracellular vesicles (MCEVs) were isolated from human postmortem ALS (n = 10) and neurological control (NC, n = 5) motor cortex brain tissues and the MCEVs protein content subsequently underwent mass spectrometry analysis, allowing for a panel of ALS-associated proteins to be identified. This panel consists of 16 statistically significant differentially packaged proteins identified in the ALS MCEVs. This includes several upregulated RNA-binding proteins which were determined through pathway analysis to be associated with stress granule dynamics. The identification of these RNA-binding proteins in the ALS MCEVs suggests there may be a relationship between ALS-associated stress granules and ALS MCEV packaging, highlighting a potential role for small extracellular vesicles such as exosomes in the pathogenesis of ALS and as potential peripheral biomarkers for ALS.